Implementation of a Hospital Medicine Rotation and Curriculum for Internal Medicine Residents - Doris Lin; Chirayu Shah; Erica Lescinskas; Cory Ritter; Lindsey Gay (Association of American Medical Colleges, 2020)
Introduction Hospital medicine is a growing field that focuses not only on expertise in inpatient medicine but also on knowledge of nonclinical health system topics. The traditional model for resident education does not lend itself to learning these topics. We developed a unique ward rotation with a dedicated curriculum called the Resident Inpatient Training Experience (RITE) to address this deficiency. Methods The RITE rotation was initially implemented in the 2013-2014 academic year. The curriculum accompanying the rotation contained four case-based modules that included content on patient safety, quality improvement, cost-conscious care, hospital metrics/reimbursement, physician billing and coding, and transitions of care. Prior to RITE, residents received an email orientation to the service. To evaluate the rotation and curriculum, residents completed a pre- and postrotation online survey. Forty-six upper PGY 2 residents each rotated on the service for 1 month. An experienced hospitalist attended on the service and facilitated a weekly discussion on each module. This publication includes an updated version of the email orientation, the four modules, and the surveys. Results There was a 72% response rate for completion of the pre- and postrotation survey. Confidence in managing hospitalized patients and knowledge of module content taught during the rotation improved. Discussion We found that implementation of a hospital medicine rotation and curriculum improved resident independence and knowledge of the module topics and was a successful way to alleviate current deficiencies in resident education.